Reappraisal of therapeutic vancomycin trough concentrations with empirical dosing in neonatal infections - Tzung-Yi Lee; Yi-Li Hung; Chung-Min Shen; Chi-Lan Kao; Wu-Shiun Hsieh (Elsevier, 2023)
Background: Vancomycin is commonly used for neonatal sepsis. However, consensus on an empirical neonatal vancomycin regimen remains uncertain. We aimed to reappraise the therapeutic optimum concerning vancomycin trough concentrations with empirical dosing and to evaluate the relationship between trough concentrations and predicted 24-h area under the curve (AUC24). Methods: This was a 3-year retrospective study. Neonates who were admitted to the neonatal intensive care unit with available vancomycin trough concentrations were enrolled. Trough levels were obtained before the fourth dose. Achievement of goal trough after implementing the vancomycin dosing regimen was based on the Practical Neonatology Medical Manual, published by the National Taiwan University College of Medicine. Results: A total of 46 neonates were included for analysis. Coagulase-negative staphylococci were the most commonly identified pathogens of sepsis. Among these patients, 22 achieved goal trough levels of 10-20 mcg/mL. Trough levels of 5-10 or >20 mcg/mL occurred in 13 and 11 patients, respectively. A moderately positive correlation between trough and predicted AUC24 was found in all patients (Spearman's rho = 0.676, p < 0.001).In patients with body weight 1200-2000 g and postnatal age >7 days, the serum creatinine of those with trough levels >20 mcg/mL was significantly higher than those with goal trough levels (0.61 vs. 0.45 mg/dL, p = 0.01). Among those with trough levels >20 mcg/mL, 5 patients received ibuprofen for patent ductus arteriosus closing prior to vancomycin treatment (45%, 5/11), compared to only 3 patients with trough levels <20 mcg/mL (9%, 3/35) (p = 0.013). Conclusion: Only half of the neonates receiving empirical vancomycin regimen achieved goal trough levels of 10-20 mcg/mL. Higher serum creatinine or ibuprofen treatment may increase the risk of overly high trough levels. The vancomycin regimen needs further validation and modification to provide adequate dosing for optimal use in neonates.